Numerical analysis of partial differential equations lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.), held in Ispra (Varese), Italy, July 3-11, 1967 - Lions, Jacques Louis (C.I.M.E. Summer Schools, 2010)
S. Albertoni: Alcuni metodi di calcolo nella teoria della diffusione dei neutroni.- I. Babuska: Optimization and numerical stability in computations.- J.H. Bramble: Error estimates in elliptic boundary value problems.- G. Capriz: The numerical approach to hydrodynamic problems.- A. Dou: Energy inequalities in an elastic cylinder.- T. Doupont: On the existence of an iterative method for the solution of elliptic difference equation with an improved work estimate.- J. Douglas, J.R. Cannon: The approximation of harmonic and parabolic functions of half-spaces from interior data.- B.E. Hubbard: Error estimates in the fixed Membrane problem.- K. Jorgens: Calculation of the spectrum of a Schrödinger operator.- A. Lasota: Contingent equations and boundary value problems.- J.L. Lions: Réduction à des problèmes du type Cauchy-Kowalewska.- J.L. Lions: Problèmes aux limites non homogènes à données irrégulières; une méthode d?approximation.- J.L. Lions: Remarques sur l?approximation régularisée de problèmes aux limites.- W.V. Petryshyn: On the approximation-solvability of nonlinear functional equations in normed linear spaces.- P.A. Raviart: Approximation des équations d?évolution par des méthodes variationnelles.- M. Sibony, H. Brezis: Méthodes d?approximation et d?itération pour les operateurs monotones.- V. Thomee: Some topics in stability theory for partial difference operators.